2018
DOI: 10.1051/metal/2018041
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hot rolling on the corrosion behavior of AZ31 magnesium alloy

Abstract: The aim of the present study is to investigate the effect of deformation conditions on the corrosion behavior of AZ31 (Mg-3Al-1Zn, % wt.) in 0.9% NaCl (wt.%) solution. The AZ31 alloy was hot rolled at 360 °C to 20 and 50% of thickness reduction. Electrochemical measurements were used to study the corrosion behavior of AZ31 alloy. Analysis of corrosion products after immersion test was performed using optical microscopy, X-ray diffraction and Raman spectroscopy. The mechanical properties of corroded samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…In this frame, the goal of this work is an investigation of the role of annealing temperature and duration on the static recrystallization/ grain growth kinetics of hot-rolled AZ31 alloy. First, the alloy was hot-rolled at 350°C to 70% of thickness reduction and then annealed at various temperatures (150°C, 250°C, and 350°C) from 5 min to 24 h. This work is a part of a series of investigations on the AZ31 alloy regarding the effect of rolling conditions and annealing treatments on corrosion behaviour [34,38]. So far, the results confirmed that small grain size combined with weak texture greatly enhanced the corrosion behavior of the AZ31 alloy [34,38].…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…In this frame, the goal of this work is an investigation of the role of annealing temperature and duration on the static recrystallization/ grain growth kinetics of hot-rolled AZ31 alloy. First, the alloy was hot-rolled at 350°C to 70% of thickness reduction and then annealed at various temperatures (150°C, 250°C, and 350°C) from 5 min to 24 h. This work is a part of a series of investigations on the AZ31 alloy regarding the effect of rolling conditions and annealing treatments on corrosion behaviour [34,38]. So far, the results confirmed that small grain size combined with weak texture greatly enhanced the corrosion behavior of the AZ31 alloy [34,38].…”
Section: Introductionmentioning
confidence: 57%
“…First, the alloy was hot-rolled at 350°C to 70% of thickness reduction and then annealed at various temperatures (150°C, 250°C, and 350°C) from 5 min to 24 h. This work is a part of a series of investigations on the AZ31 alloy regarding the effect of rolling conditions and annealing treatments on corrosion behaviour [34,38]. So far, the results confirmed that small grain size combined with weak texture greatly enhanced the corrosion behavior of the AZ31 alloy [34,38]. It is believed that the present work will help to provide more data to ameliorate the design of AZ31 alloy.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the grain refinement produced by SPD processing leads to a uniform corrosion due to the increase in grain boundary numbers which improves the corrosion properties of Mg-based alloys. In practice, in many cases it is found that improving the strength and formability of the Mg-RE alloys have a negative effect on the corrosion performance [15,[51][52][53]. The increase in dislocation density and the presence of twins appear to decrease the corrosion resistance of deformed Mg-based alloys [49].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, challenging analyses must be conducted to optimise the distribution of second phases to obtain uniform corrosion in Mgbased alloys. Thermo-mechanical processing and/or alloying elements have proven their effectiveness in modifying the microstructure by decreasing grain size as well as changing the distribution of second phases [7][8][9][10][11][12][13][14][15]. For example, high-pressure torsion (HPT) processing leads to uniform corrosion compared to localised corrosion, as occurs in as-cast pure Mg [9].…”
Section: Introductionmentioning
confidence: 99%